ANALYSIS OF THE EFFECT OF FACILITATING CONDITIONS AND ELECTRONIC WORDS OF MOUTH ON AIRLINES TICKET PURCHASE DECISION THROUGH TRUST AS A MEDIATING VARIABLE - Sudarman, Daman; Sabaruddin, Sabaruddin (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
In today's digital age, technology advancements have transformed how consumers buy airline tickets, with facilitating conditions, Electronic Word of Mouth (EWOM), and trust playing pivotal roles in the decision-making process. Understanding these factors through the UTAUT can help airlines and travel agencies enhance their digital platforms and marketing strategies. The study aims to determine the effect of technology acceptance (UTAUT) variables, namely performance expectancy, effort expectancy, social influence, facilitating conditions, Electronic Words of Mouth (EWOM), and trust, in the decision to purchase airline tickets online in Indonesia. The study used a purposive sampling technique and structural equation modelling to test the research hypothesis. This study used an online research questionnaire survey technique for 253 respondents. The results of the study show that the UTAUT dimension performance expectancy with t-statistic 2.207>1.96, effort expectancy (2.068>1.96), facilitating condition (2.085>1.96), and EWOM (2.348>1.96) influence online ticket purchase decisions. The social influence dimension doesn’t influence purchase decisions with t-statistics 0.618<1.96. The study also found that Trust mediates the relationship between performance expectancy with coefficient score (0.061), effort expectancy (0.044), facilitating conditions (0.054), and EWOM (0.042) on purchasing decisions